2016
DOI: 10.1120/jacmp.v17i1.5774
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MVCT imaging dose levels during helical IGRT: comparison between ion chamber, TLD, and EBT3 films

Abstract: The purpose of this investigation was to evaluate the dose on megavoltage CT (MVCT) images required for tomotherapy. As imaging possibilities are often used before each treatment and usually used several times before the session, we tried to evaluate the dose delivered during the procedure. For each scanning mode (fine, normal, and coarse), we first established the relative variation of these doses according to different technical parameters (explored length, patient setup). These dose variations measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Our results (the maximum absorbed doses to parotids, lungs and bladder) were compared with the MSADs reported by Mege et al [8], which were delivered to three clinical sites (head and neck, thorax, and pelvis [abdomen]). Our results were 17.2% lower than the average MSADs reported in Mege et al One reason for this difference is the difference in the MVCT dose levels.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Our results (the maximum absorbed doses to parotids, lungs and bladder) were compared with the MSADs reported by Mege et al [8], which were delivered to three clinical sites (head and neck, thorax, and pelvis [abdomen]). Our results were 17.2% lower than the average MSADs reported in Mege et al One reason for this difference is the difference in the MVCT dose levels.…”
Section: Discussionmentioning
confidence: 86%
“…The reason for this is that Jeraj et al reported that the average energy of the MVCT beam is close to that of treatment beam [11]. In a study by Mege et al , the conversion factor for measuring the point dose from MVCT delivery was taken as that for the 6 MV treatment beam due to the small difference between the average energy of the MVCT beam and the treatment beam [8]. In AAPM TG-148, no correction of the conversion factor for the treatment beam to use for the imaging beam was recommended [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Users can choose among three different MVCT slice thickness: fine (2 mm), normal (4 mm) and coarse (6 mm), resulting in variable imaging durations (Yartsev et al 2007), image qualities and absorbed doses (Shah et al 2008, Mege et al 2016. The maximum acquisition length is 150 cm and the Field of View is 39 cm (512 × 512 pixels).…”
Section: Mvct Acquisition Protocols and Image Registration Optionsmentioning
confidence: 99%